Pengembangan Instrumen Penilaian Karakter Inisiatif Belajar Siswa Pasca Pandemi di SMA Negeri 2 Binjai - Deby Octavia Tambunan; Rosmala Dewi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2023)
The objectives of this study were to (1) develop a valid student learning initiative character assessment instrument for use in high school, (2) develop a practical student learning initiative character assessment instrument for use in high school (3) analyze the validity and practicality of the learning initiative character assessment instrument. developed for use in high school. The study used the Research and Development (RnD) method with the ADDIE model (Analysis, Design, Development, Implementation,  Evaluation). The population in this study were students of class XI SMA Negeri 2 Binjai. The sample used is class XI PMS 1,2,3,4,5,6,7 and class XI PIS 1,2,3,4,5 totaling 17 people for each class. The sampling technique used is simple random sampling with the Slovin formula. The results obtained  are  products in the form of a character assessment instrument for student learning initiatives with the type of observation sheet for teacher assessment and a  situational judgment test for student self-assessment. The items on the observation sheet were declared valid by experts with a score of 85%, and reliable with reliability > 0.7. Likewise with the situational test, the item is declared valid and reliable with Product Moment values > 0.138 and α-Cronbach > 0.813. Both instruments are also declared practical based on the value of practicality > 90%. Based on the results and discussion, it can be concluded that the character assessment instrument developed is feasible to be used in assessing the character quality of student learning initiatives in high school.